RANCANGAN SISTEM OTOMATIS CHLORINATOR PADA DISTRIBUSI AIR BERSIH DI BANDAR UDARA INTERNATIONAL SOEKARNO-HATTA - Lukman Pambudi; KGS. M. Ismail; Harman Sudjanto (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Chlorinator is processing a chlorine solution (mix chlorine with water) and the solution will be injected using dosing pumps into clean water that will be distributed throughout the Soekarno-Hatta airport. In this design the automatic control chlorinator system using a microcontroller arduino uno (ATmega 328P). To drain the chlorine into the measuring tube using a solenoid valve that works automatically stop working when a small float in the measuring tube reaches the maximum limit. Then to keep the solution in the tank from being discharged chlorinator uses a float sensor. Sensor buoys will work to enable the water pump and solenoid valve when the volume of the solution under 260 liters